Incremental Value of Pocket‐Sized Echocardiography in Addition to Physical Examination during Inpatient Cardiology Evaluation: A Multicenter Italian Study (SIEC). Issue 10 (12th April 2015) - Di Bello, Vitantonio; La Carrubba, Salvatore; Conte, Lorenzo; Fabiani, Iacopo; Posteraro, Alfredo; Antonini‐Canterin, Francesco; Barletta, Valentina; Nicastro, Irene; Mariotti, Egidio; Severino, Sergio; Caso, Pio; Benedetto, Frank; et al.
<x xml:space="preserve">Abstract</x> Background We prospectively assessed the incremental value of a pocket‐sized echocardiography (PSE) device during cardiology consultations, in addition to physical examination, ECG reading, and chest x‐ray. Methods A total of 443 consecutive patients (53% men), referred for bedside consultations, underwent physical examination, ECG, and CXR, followed by PSE examination. The physician completed a detailed questionnaire (clinical and echocardiographic data, scanning time, abnormal results). Receiver operating characteristic (ROC) curve analysis was generated to test the predictive discrimination value of the different methods. The incremental value of PSE examination compared to clinical visit alone or combined with ECG results was expressed as a global chi‐square value. Results The PSE examination did not influence the definitive diagnosis in only 23.5% of cases, while 25.3% of the diagnoses were confirmed and verified by PSE. The clinical diagnosis was enriched by PSE in 21.9% of cases, and the diagnosis was changed in 26.2%. The area under curve (AUC) of physical examination + ECG results (sensitivity: 80%; specificity: 67%) was significantly higher than physical examination alone (sensitivity: 75%; specificity: 62%) (P < 0.0002), and the AUC of PSE results (sensitivity: 88%; specificity: 86%) was significantly higher than physical examination + ECG results (P < 0.0001). The PSE results, combined with clinical and ECG results, had a significant incremental diagnostic value during cardiology consultation when compared to the clinical visit alone or with ECG results (P < 0.0001). Conclusions PSE had an incremental diagnostic value during bedside cardiology consultation, increasing the number of appropriate diagnoses and reducing the routine use of echocardiography.